Juridical Review of The Existence of Tourism Electric Cars in The City of Surakarta based on Law Number 22 of 2009 (Case Study at the Surakarta City Transportation Department) - Devandra Alzamora Mahatma Rafshanzany; Nunik Nurhayati (Proceeding International Conference Restructuring and Transforming Law, 2023)
The presence of tourist electric cars in Surakarta City as a tourist transport reaped various polemics that developed in society. It happened because there are no clear regulations regarding licensing mechanisms, type tests, periodic tests, safety and eligibility criteria for these vehicles. The purpose of this research is to find out and analyze: (1) the mechanism for operational licensing, type testing, and periodic testing of tourist electric cars and (2) reviewing of the safety and the eligibility criteria for tourist electric cars. The method that used in this research is qualitative descriptive method with a literature study approach derived from legal books, literature, and applicable laws and regulations. The results of the study found that: (1) Tourist electric cars in Surakarta City have not carried out operational permits, type tests, periodic tests as they should, (2) as well as safety and eligibility criteria which are quite enough to be used as tourist transportation.